Employee perceptions of support for family friendly initiatives in the workplace : a thesis submitted in partial fulfilment of the requirements for the degree of Master of Arts in Psychology at Massey University - McAulay, Fiona Elizabeth (Massey University, 1999)
The present research investigated the relationships between levels of work-family/family-work conflict, the use of family friendly initiatives, and levels of perceived supervisor, co-worker, and overall organisational support. It has been suggested that the use and effectiveness of family friendly initiatives may be compromised due to unsupportive supervisor attitudes, co-workers, and organisational cultures. Thus, the relative importance of family friendly initiatives and informal workplace supports for the reduction of work-family conflict, and the influence of informal workplace supports on the use of these initiatives were of particular interest. Participants were employees in four medium to large organisations that were members of the Equal Employment Opportunities Trust, Work and Family Network. A questionnaire was developed that included existing scales as well as original items. Overall, 279 male and female employees returned useable questionnaires (a response rate of 37%). No significant relationships were found between the use of family friendly initiatives and work-family or family-work conflict. However, significant relationships were found between levels of work-family conflict and supervisor, co-worker, and overall workplace support. These informal workplace supportive variables were also shown to be more important to the prediction of work-family and family-work conflict, than was the use of family friendly initiatives. Levels of work-family conflict were greater for men than for women, and men's use of family friendly initiatives was significantly related to their perceptions of informal workplace support. No such relationship was found for women. The research demonstrated that informal workplace support was more important to the reduction of work-family and family-work conflict than the number of initiatives used. The importance of work-family conflict to men was highlighted, demonstrating the relevance of family friendly initiatives for both genders. The attitudes and expectations in the workplace that limit the use of initiatives, particularly by men, need to be changed. When introducing a family friendly programme, the needs of employees, the quality of the initiatives, the attitudes of supervisors and co-workers, and the expectations and structure of work within the organisation, must all be addressed to ensure that employees feel able to make use of the family friendly initiatives available.
Keywords: Work and family; Working mothers; New Zealand